FAKTOR PENAWARAN YANG MEMPENGERUHI KOPI ARABIKA (Coffea arabica L) TERHADAP PENDAPATAN PETANI BENTUK BUAH PANEN. - Fandri Siburian; Posman HP Marpaung (JURNAL AGROTEKNOSAINS, 2022)
The agricultural sector has a very important role in building the economy in Indonesia. Because in this sector its role is related to providing employment, providing food, contributing to foreign exchange through exports and so on. With the strength of the agricultural sector in terms of supply and demand, agriculture will be able to support and establish links with other sectors of economic activity. The agricultural sector itself has several sub-sectors, including food crops or food crops sub-sector (better known as smallholder agriculture), plantation sub-sector, livestock sub-sector, forestry sub-sector, and fishery sub-sector. One of the plantation commodities that deserves to be developed to build economic resilience is Arabica coffee. In Indonesia, Arabica coffee is one of the plantation crops that has a strategic role and has the opportunity to be developed, because Arabica coffee is the main source of industrial raw materials. At first the use of Arabica coffee beans was dominated for direct consumption. However, currently the use of Arabica coffee beans is mostly used for industrial needs with various types of coffee drinks being produced and coupled with the increasing number of requests along with the increase in population and the increasing need for industrial raw materials in Indonesia. Supply is the number of agricultural commodities offered by producers or sellers. Meanwhile, the law of supply basically states that the higher the price of an item, the more the quantity of that item will be offered by producers/sellers assuming other factors do not change. The total supply of a good is the total production of each unit of production in one production period plus the remainder from the previous period. If production is driven by net income, changes in agricultural output are due to changes in relative prices. The supply curve of a firm represents the maximum quantity of goods that are willing to be produced for sale at any given time, at various price levels